The Reception Given to Sadhu Sundar Singh, the Itinerant Indian Christian 'Mystic', in Interwar Britain. Issue 1 (2nd January 2017) - Mukherjee, Sumita
Abstract: In 1920 and 1922, an Indian Christian called Sadhu Sundar Singh toured Britain. Widely renowned in the global Christian community in the interwar period, Singh was notorious for certain stories of miracles, for his appearance and for the ways in which he epitomised Eastern Christianity. Using Singh's correspondence and a range of newspapers, this article argues that British audiences were attracted to Singh because of his appearance and ethnicity and because he conformed to stereotypes of essentialised Indian spirituality despite his Christian faith. It argues that the reception to Singh in Britain must be understood in relation to the perpetuation of Orientalist understandings of Indians and Indian religions in the interwar period.